The 2011 expedition to the El'gygytgyn impact structure, Northeast Russia: Toward a new geological map for the crater area. (29th May 2014) - Raschke, Ulli; Zaag, Patrice Tristan; Schmitt, Ralf Thomas; Reimold, Wolf Uwe
Abstract El'gygytgyn is a 3.6 Ma, 18 km diameter, impact crater formed in an approximately 88 Ma old volcanic target in Northeast Siberia. The structure has been the subject of a recent ICDP drilling project. In parallel to those efforts, a Russian‐German expedition was undertaken in summer 2011 to investigate the permafrost soil, lake terraces, and the volcanic rocks of the southern and eastern crater rim. This provided the unique opportunity for mapping and sampling of the volcanic target rocks around a large part of this complex impact structure. Samples from 43 outcrops were collected and analyzed petrographically and geochemically. The results were combined with earlier mapping outcomes to create a new geological map of this impact structure and its immediate environs, at the scale of 1:50, 000. Compositions of our rock suites are compared with the lithologies of the 2009 ICDP drill core. The ignimbrite described as lower bedrock in the ICDP drill core shows petrographically and chemically strong similarities to the rhyolitic and rhyodacitic ignimbrites observed on surface. The suevite sequence exposed in the ICDP drill core is a mixture of all observed target rocks at their respective proportions in the area. In contrast to previous studies, the calculated average target composition of El'gygytgyn takes the contribution of the basic target rocks into consideration: mafic and intermediate rocks approximately 7.5%, and felsic rocks approximately 92.5%.